3D-QSAR study of competitive inhibitor for acethylcholine esterase (AChE) nerve agent toxicity - Juan, Amor A. San; Cho, Seung Joo (KOREAN SOC TOXICOGENOMICS & TOXICOPROTEOMICS, 2006)
The cholinesterase-inhibiting organophosphorous (OP) compounds known as nerve agents are highly toxic. The principal toxic mechanism of OP compounds is the inhibition of acethylcholine esterase (AChE) by phosphorylation of its catalytic site. The reversible competitive inhibition of AChE may prevent the subsequent OP intoxication. In this study, three-dimensional quantitative structure-activity relationship (3D-QSAR) was performed to investigate the relationship between the 29 compounds with structural diversity and their bioactivities against AChE. In particular, predictive models were constructed using the comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA). The results indicate reasonable model for CoMFA (q(2) =0.453, r(2)= 0.697) and CoMSIA (q(2)= 0.518, r(2) = 0.696). The presence of steric and hydophobic group at naphtyl moiety of the model may lead to the design of improved competitive inhibitors for organophosphorous intoxication.
Keywords: NONQUATERNARY CHOLINESTERASE REACTIVATORS; METHYLPHOSPHONYL-ACETYLCHOLINESTERASE INVITRO; ETHYL METHYLPHOSPHONYL